Agronomic performance and combining ability estimates of yellow maize inbred lines under adequate and deficit moisture conditions (2022)
Breeding for drought tolerance and increased grain yield is vital in mitigating the threat posed by recurrent drought stress on maize production, as well as tackling malnutrition with plant-based food products. The study was conducted to assess the combining ability of yellow maize lines and the performance of their single-cross hybrids under drought and rain-fed conditions. A total of 24 yellow maize inbred lines from CSIR-Savanna Agricultural Research Institute Maize Improvement Programme gene pool were selected and inter-mated using North Carolina II mating design to generate 96 single-cross hybrids. The 96 hybrids together with four advanced hybrids used as checks (a total of 100 hybrids) were evaluated under drought and rain-fed conditions for two years using a 10 × 10 lattice design with two replications. The hybrids differed significantly in their grain yield (GY) and agronomic performance under the growing conditions. In the present study, drought stress reduced GY by 50.3%. The general combining ability (GCA) and specific combining ability (SCA) for GY and its related traits were significant. Even though additive and non-additive gene actions controlled the inheritance of the traits, additive gene action was found to be more important than non-additive genetic effects. Hybrids 27, 81 and 68 on the other hand 89, 18 and 26 were identified as the outstanding genotypes under drought and rain-fed conditions, respectively. These hybrids should be extensively evaluated under varied conditions and commercialized to enhance food insecurity in sub-Saharan Africa.